Washingtonia 1829: an American refugee colony in Greece - Kourelis, Kostis; Pettegrew, David K.; Poulopoulos, Nikos; Sarvis, Albert; Shehigian, Alexandra (Journal of Greek Archaeology, 2025)
The founding of the colony of Washingtonia at Ano Examilia on the Isthmus of Corinth represents a unique, forgotten episode of collaborative humanitarianism at the birth of the Greek nation-state. Established in 1829 by Samuel Gridley Howe and his colleagues, funded by American citizens, and chartered by Governor Ioannis Kapodistrias, the settlement housed several dozen migrant families displaced during the Greek War of Independence (1821-1829). Within a few years, refugees successfully cultivated an agricultural district of the Isthmus and built or rebuilt houses, hospital, school, church, and port facilities. Although the memory of the original colonists soon disappeared and the settlement’s name ‘Washingtonia’ returned to its earlier name of Examilia, the colony served to revitalize an important Corinthian village after the war. The establishment of Washingtonia was significant as a pioneering transnational intervention in which utopian experiments of cooperative farming in the U.S. could be put into action by Greek refugees halfway around the world.